Synthesis and Antifungal Activity of 2-Phenylimino-5-Aryl/ Alkylimino-1,3,4-Thiadiazolidines - R.S. Deshmukh, Ms.; Bhaskar, C.S.; Berad, B.N. (Asian Journal of Chemistry, 2010)
Synthesis of several 2-phenylimino-5-aryl/alkylimino-1,3,4-thiadiazolidines (IV) have been reported by a new route. The interaction of aryl/alkyl thiosemicarbazides (I) and N-phenyl isocyano dichloride (II) in refluxing chloroform medium for 3 h afforded 2-phenylimino-5-aryl/alkylimino-1, 3, 4-thiadiazolidines hydrochlorides (III) which on basification with dilute ammonium hydroxide solution gave title compounds (IV). Title compunds on acetylation in 1 : 1 ratio gave monoacetyl derivatives (V). The structures of all these compounds were established on the basis of elemental analysis, equivalent weight determination and IR and PMR spectal studies. The synthesized compounds were assayed for their antifungal activity against tuber fungus Rhizoctonia bataticola with encouraging results.